Localization and steric effect of the lone electron pair of the tellurium Te4+ cation and other cations of the p‐block elements. A systematic study. Issue 5 (8th September 2020) - Hamani, D.; Masson, O.; Thomas, P.
Abstract : This article presents a geometrical method to localize and model the steric effect of lone pairs (LPs) of cations of the p ‐block elements as well as the trends of the LP size and displacement from the cation core in the periodic table. Abstract : A simple method has been developed based on pure geometrical concepts to localize lone pairs (LPs) of cations of the p ‐block elements and model their steric effect. The method was applied to 1185 structures containing LP cations in 2439 non‐equivalent positions. For oxide crystal structures, it is observed that, going from bottom left to top right in the periodic table, LPs move away from the cation core and decrease in size. For a given kind of cation M*, the LP radius increases linearly with the M*–LP distance, the smallest rate being observed for Tl + and the largest for Cl 5+ . The influence of the anion type was also studied in the case of the Te 4+ cation. Overall, the same trends were observed. The smallest Te–LP distances and LP radii are found for anions of large size and small charge.